Implikasi Pola Makan Tinggi Natrium Terhadap Kejadian Hipertensi di Masyarakat Pesisir - Prasetyowati, Irma; Puspitasari, Muthia Fahriyah; Putri, Syafira Aurellia; Ayunni, Kartika Astri Firda; Thoyiba, Nuzula Lailatul; Hilmiy, Daryta Balqis Nashifa; Nurmusfiroh, Rizqi Faza; Zahro, Adinda Khatimatuz; Salsabilah, Della Estelina; Wijaya, Novita Dian Rahmawati (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: Hypertension, commonly referred to as "the silent killer," has become one of the degenerative diseases that still show high case numbers in society. Coastal communities are one of the groups that can experience hypertension due to diet, limited access to healthcare services, and other factors. This study was conducted to analyze non-modifiable risk factors (age, gender, family history) and modifiable risk factors (diet, physical activity, occupation, education, smoking behavior, access to healthcare services) associated with the incidence of hypertension.Methods: The research uses an analytical and cross-sectional with a sample size of 127 people through simple random sampling using the Chi-square test with a 95% confidence level (α = 0.05). The variables used in this study are age, gender, family history, education, occupation, economic status, diet assessed using the Food Frequency Questionnaire (FFQ), physical activity evaluated using the Global Physical Activity Questionnaire (IPAQ), smoking behavior, and access to health services.Result: Based on the risk factors studied, there was a significant association between diet (p = 0.001 & PR 1.534), education (p = 0.000 & PR 1.766), and age (p = 0.038 & PR 1.301) with the incidence of hypertension. However, other variables such as gender, family history, economic status, access to health facilities, physical activity, and occupation did not have a significant relationship with hypertension.Conclusion : The research shows a significant relationship between dietary patterns, education, and age with the incidence of hypertension in coastal communities.